Beyond the boom - Edwards, John (Penguin Group, 2014)
After decades of prosperity Australians are now worried about their jobs, their incomes and their future. The mining boom, said to explain Australia's past success, is declared to be over. Unemployment has increased, carmakers have folded, the government is running a huge deficit. In a striking analysis, economist John Edwards challenges the prevailing pessimism. Cutting through the confusion, Edwards shows that the mining boom is far from over - and that it hasn't been as important for Australian prosperity as widely believed. We have a bright future in the world, and the economy is well configured to get us there. The bright future won't be in what we dig, though. It will be in what we grow, what we make and, above all, in the services we provide.